Adopting howard gardner’s multiple intelligence theory (MIT) into the 21st century social studies classroom (2020)
Social Studies came as a corrective study with staunch commitment of grooming and repositioning citizens to acquire required knowledge, skills, attitude and values necessary for active participation in societal activities. The purpose of the Social Studies curriculum is to allow students become smart thinkers who proffer plausible solution to personal, community and world problems. Traditional Social Studies classroom is identified with concepts and themes like multidisciplinary field, learner as empty slate (tabula rasa), teacher-centered approach, convergent learning and so on. With the introduction and adoption of Howard Gardner’s multiple intelligence theory in the 21s1 century Social Studies classroom, the conventional means of teaching and learning will fizzle into oblivion. The resultant effect tends to be integrated approach of teaching-learning, learners as pathfinders, teachers as facilitators, and above all experiential learning. This study therefore advocates for modern Social Studies classroom which addresses core issues around human beings and places learners at the centre of all that transpires in classroom setting. Students should be shown the world, not just talk about it, but a restoration of joy of learning into the 21s' century Social Studies classroom where there is curriculum of role plays, simulations, and demonstrations that can bring alive social dynamics within the classroom. Modern Social Studies classroom should be entrusted in the hands of professionally trained Social Studies educationists.